Classification of rock types of porous limestone reservoirs: case study of the A oilfield - Huang, Tingting; Chen, Mingjiang; Wang, Xia; Duan, Guanghui; Fu, Meiyan (Frontiers in Earth Science, 2024)
Rock type with similar lithological component and pore structure is the basic unit in the porous limestone reservoir, which can influence the reservoir evaluation efficiency and water injection development. As the main oil and gas pay zone in the central Iraq, the Cretaceous Khasib Formation reservoirs are controlled by deposition, dissolution and cementation. There was strong vertical heterogeneity in the most important zone of Kh2 layer, with diverse rock types and complex pore structure. Based on core observation and casting thin section identification, the Kh2 layer in the study area can be divided into eight lithofacies types, e.g. argillaceous bioclastic wackestone, planktic foraminiferium wackestone, lamellar bioclastic wackestone, intraclastic-bioclastic packstone, patchy green algae packstone, green algae-pelletoid packstone, benthic foraminiferium-bioclastic packstone and intraclastic grainstone. Combined with the reservoir void space types of lithofacies, capillary pressure curve is used to quantitatively analyze the throat and pore features of different lithofacies.According to the porosity-permeability cross plot characteristics and distribution of pore types, 14 petrophysical facies are divided. Finally, in terms of the differences of lithofacies and petrophysical facies, the Kh2 member is divided into 13 rock types with different geological origin and petrophysical characteristics. Among them, the rock type RT1-8-14 has the best physical properties of reservoir rock types. The rock type RT1-1-1 has the worst physical properties of reservoir rock types. This study provides a optimization methods for the carbonate reservoir evaluation and be beneficial for the efficient development of similar carbonate reservoir.